Removal of Congo Red (Dye) by Using Chemically Modified Sawdust - Kulkarni, J.R.; Shrivastava, V.S. (Asian Journal of Chemistry, 2016)
Removal of Congo Red dye from an aqueous solution has been studied using sorbent prepared from sawdust treated with HCHO and dil. H2SO4. The effects of pH, contact time, sorbent dose and initial dye concentration have been studied. Effect of diverse ions has also been studied. The optimum removal is obtained at pH = 6, 90 min time of contact, 1 g of sorbent dose and low dye concentration. The amount of dye adsorbed per g of sorbent increases with increasing initial concentration. Different light metals and other ions do not affect the system.